EFFECT OF DIFFERENT FEEDS AND WATER SALINITIES ON THE CYST PRODUCTION OF BRINE SHRIMP, ARTEMIA SP. - Vartak, V. R.; Joshi, V. P. (Journal of Indian Fisheries Association, 2015)
Effect of different feeds and salinities on cyst production in Artemia sp. was studied. Among the 12 different feeds used, ragi powder suspension showed the best growth and cyst production. A wide range of salinity from 90 to 210 %o was used to study its effect on cyst production. Among all these treatments, 130 %o salinity was found suitable for induction of oviparity and cyst production in the San Francisco Bay strain of Artemia sp. Keywords : Artemia sp., oviparity, cyst, feeds, reproductive capacity